Quantifying the mechanical work of breathing in men and women during rowing - Reinhard, P. A.; Gerson, E. A.; Sheel, A. W.; Archiza, B. (European Journal of Applied Physiology, 2020)
Purpose: To quantify the mechanical work of breathing (Wb) during an indoor rowing test in men and women. Additionally, to compare sex-based differences in the Wb and its components through a rowing test. Methods: Fifteen collegiate rowers were recruited (8 women/7 men) and performed a 2000 m rowing test on a rowing ergometer. Esophageal pressure was measured during exercise via balloon catheterization, after which pressure-volume curves were used to calculate total, inspiratory resistive and elastic, and total expiratory Wb. Results: Men had significantly higher values of instantaneous and cumulative total Wb at and beyond 37.5% (430.4 ± 42.5 vs. 282.1 ± 45.1 J/min, P < 0.05) and 62.5% (1946.8 ± 150.9 vs. 1360.1 ± 197.2 J, P < 0.05) total exercise time, respectively. However, when compared at the same minute ventilation, women had higher values of total (at and above ~ 140 L/min), inspiratory resistive (at and above ~ 120 L/min), and inspiratory elastic (at and above ~ 135 L/min) Wb, whereas men presented higher total expiratory Wb compared to women at any ventilation. Conclusion: Although female rowers present higher relative values of inspiratory resistive and elastic Wb, their male counterparts develop greater ventilatory efforts during a 2000 m rowing test, resulting in a larger total mechanical Wb. We interpret these findings to mean that the Wb reflects both anatomical (i.e., airways and lung sizes) and respiratory (i.e., minute ventilation) sex differences during rowing.